Eye-tracking does not reveal early attention processing of sexual copulatory movement in heterosexual men and women - Vaníček, Ondřej; Krejčová, Lucie; Hůla, Martin; Potyszová, Kateřina; Klapilová, Kateřina; Bártová, Klára (Scientific reports, 2024)
Men and women respond differently when presented with sexual stimuli. Men's reaction is gender-specific, and women's reaction is gender-nonspecific. This might be a result of differential cognitive processing of sexual cues, namely copulatory movement (CM), which is present in almost every dynamic erotic stimulus. A novelty eye-tracking procedure was developed to assess the saliency of short film clips containing CM or non-CM sexual activities. Results from 29 gynephilic men and 31 androphilic women showed only small and insignificant effects in attention bias and no effects in attentional capture. Our results suggest that CM is not processed differently in men and women and, therefore, is not the reason behind gender-nonspecific sexual responses in women.
Keywords: Eye-Tracking Technology; Copulation; Animals; mužské pohlaví; heterosexualita; Sexual Behavior; ženské pohlaví; zvířata; Humans; kopulace; Heterosexuality; Female; Attentional Bias; sexuální chování; odklon pozornosti; lidé; Male; technologie sledování pohybu očí